Periostin antisense oligonucleotide prevents hepatic steatosis and fibrosis in a mouse model of non‐alcoholic steatohepatitis. Issue 12 (13th May 2020) - Kobayashi, Tomoki; Kanno, Keishi; Nguyen, Phuong Thao; Sugiyama, Akiko; Kawahara, Akihiro; Otani, Yuichiro; Kishikawa, Nobusuke; Ito, Masanori; Tazuma, Susumu
Abstract: Background and Aim: Non‐alcoholic steatohepatitis (NASH) is characterized by hepatic steatosis, inflammation, and hepatocellular injury with varying degrees of fibrosis. There are currently no established treatment approaches for NASH other than lifestyle interventions. Periostin, a matricellular protein required for tissue remodeling and fibrosis, plays an important role in hepatic steatosis and fibrosis and could be a potential target for NASH treatment. Advances in molecular biology and biochemical engineering have led to the development of antisense oligonucleotides (ASOs) that can inhibit target genes with no significant toxic effects. Herein, we investigated the therapeutic effects of periostin‐targeting ASO (PNASO) in NASH. Methods: C57BL/6J mice were fed a choline‐deficient, l ‐amino acid‐defined, high‐fat diet (CDAHFD) to induce NASH with or without intraperitoneal injection of mouse PNASO. To explore the role of periostin in hepatocellular steatosis, Hc3716 cells, an immortalized human hepatocyte line, were treated with recombinant periostin in vitro . Results: The induced periostin expression in the liver of CDAHFD‐fed mice was significantly suppressed by PNASO. The deletion of hepatic periostin by PNASO significantly ameliorated hepatic steatosis while restoring the expression levels of peroxisome proliferator‐activated receptor‐alpha ( PPAR‐α ) and its target genes. PNASO also inhibited hepatic fibrosis, reflected by the reduction of alpha‐smooth muscle actin, collagen type I, and other fibrotic markers. In vitro experiments demonstrated that treatment with recombinant periostin increased cellular lipid accumulation in Hc3716 cells accompanied with the downregulation of PPAR‐α. Conclusions: Periostin‐targeting ASO is a potential therapeutic approach for the efficient treatment of hepatic steatosis and fibrosis in NASH.